Influence of multiple endorser-product patterns on purchase intention: An interpretation of elaboration likelihood model. Issue 4 (5th November 2018) - Liang, Huai-Liang; Lin, Ping-I
Abstract : Purpose: Enterprises must select the best optimal endorser-product fit in order to maximize the limited budget available for endorsements. Previous studies have determined that the influence of athlete endorsers is greater than is that of celebrity endorsers on consumer attitudes toward sport products. However, different endorsers may possess different levels of influence on products. The paper aims to discuss these issues. Design/methodology/approach: This study developed two field experiments to investigate the influence of endorser-product fits on consumer purchase intentions. Participants in Study 1 were 295 individuals (220 male consumers, 75 female consumers, M age=32 yr) in the two Baseball Stadiums in Taiwan. Participants in Study 2 were 317 EMBA students (204 men, 113 women, M age=34 yr) at a certain university in Taiwan. Findings: The results determined no significant moderating effect of celebrity endorser-product fit and purchase intention, whereas athlete endorser-product fit enhanced consumers' purchase intentions in low product involvement scenarios. In high product involvement scenarios, a moderating relationship between endorser-product fit and purchase intentions was observed. These findings can provide a reference regarding endorsers and product patterns for enterprises to maximize the value of endorsers. Originality/value: Using the multiple endorser-product patterns, this study provides useful findings in terms of the perceived value of endorser-product and purchase intention. The results of this study can help enterprises to choose the most suitable endorser when they are subject to budget constraints. Detailed descriptions of the expected results and discussion are reported in the text.